CHRONIC INFLAMMATORY LESIONS OF THE GROIN IN A PATIENT WITH SCHIZOPHRENIA DURING LONG-TERM POLYPHARMACOTHERAPY: A POTENTIAL ADVERSE EFFECT OF ANTIPSYCHOTIC DRUGS - Nieradka, Kaja; Klahs, Krystyna; Muraszko-Kuźma, Maciej; Twardy, Patryk; Wagner, Weronika; Białożyt, Jakub; Dębniak, Anna; Gutarowicz, Maciej; Modelewski, Patryk; Armatys, Michał (International Journal of Innovative Technologies in Social Science, 2026)
Objective: This paper presents a case report of a patient with recurrent skin lesions of probable drug-induced etiology. The study highlights the importance of considering adverse drug reactions. Methods: A detailed clinical interview, medical documentation, and the patient’s pharmacological treatment were analyzed, with particular emphasis on the potential adverse effects of the medications used. The analysis included an assessment of the temporal relationship between the administered drugs and the occurrence of skin lesions, as well as the exclusion of other possible causes, including infectious etiologies. Particular attention was paid to the possibility of a drug-induced nature of the observed lesions. Key Findings: A patient with long-standing schizophrenia receiving extensive polypharmacotherapy developed chronic inflammatory lesions in the groin area. Comprehensive diagnostic evaluation excluded infectious causes, indicating a probable drug-induced etiology of the lesions. This case highlights the importance of considering adverse drug reactions and polypharmacotherapy in the diagnostic process of chronic skin lesions. Conclusions: By presenting this case, we aim to emphasize that chronic skin lesions in patients undergoing long-term polypharmacotherapy may most likely be drug-induced, particularly after infectious causes have been excluded. In clinical practice, careful attention should be paid to the medications the patient is taking, as well as to potential drug interactions and adverse effects. With appropriate medical supervision, however, the condition may remain stable and well controlled.